2022
DOI: 10.1177/02666669221114649
|View full text |Cite
|
Sign up to set email alerts
|

The predictors of mobile government services adoption through social media: A case of Chinese citizens

Abstract: This research studied the factors accounting for Chinese citizens’ behavioral adoption of mobile government services via social media platforms. Social media innovations have empowered governments to better interact and stay in touch with citizens, and thus understanding citizens’ adoption of government services via social media will enable policymakers to leverage social media to better meet the service requirements of citizens. Drawing upon the Chinese mobile-government context, this research framework was m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 124 publications
0
2
0
Order By: Relevance
“…Moreover, it was found that recent studies have focused on the adoption of m-government (Fu et al, 2022;Mensah et al, 2023;Mensah & Mwakapesa, 2022). One study has focused on continuance intention; however, this study has not provided statistical analysis, as the aim was to validate research items and the number participants did not exceed ninety (Alshammari et al, 2022).…”
Section: Current State Of M-governmentmentioning
confidence: 99%
“…Moreover, it was found that recent studies have focused on the adoption of m-government (Fu et al, 2022;Mensah et al, 2023;Mensah & Mwakapesa, 2022). One study has focused on continuance intention; however, this study has not provided statistical analysis, as the aim was to validate research items and the number participants did not exceed ninety (Alshammari et al, 2022).…”
Section: Current State Of M-governmentmentioning
confidence: 99%
“…Compared with alternative consumer adoption of technology theories, such as the Technology Acceptance Model (TAM) [ 54 ] and the Unified Theory of Acceptance and Use of Technology (UTAUT) [ 55 ], the updated DeLone and McLean ISSM allows for a more thorough evaluation of the success of mGovernment apps, considering various influencing dimensions. In this study, the quality of mGovernment apps is examined using three dimensions, namely: system quality, service quality, and information quality.…”
Section: Research Hypotheses and Modelmentioning
confidence: 99%